2017
DOI: 10.1136/openhrt-2016-000551
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure following STEMI: a contemporary cohort study of incidence and prognostic factors

Abstract: ObjectiveThe aim of the current study was to determine the contemporary incidence, risk factors and prognosis of heart failure (HF) after ST-elevation myocardial infarction (STEMI).MethodsWe used the Arrhythmia Genetics in the Netherlands observational cohort study to identify patients with a first STEMI from 2001 onwards (n=1459). HF during follow-up was defined as hospitalisation for HF or an outpatient clinic visit for HF. Cox regression was performed to estimate the relationship between baseline covariates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
(28 reference statements)
2
24
0
2
Order By: Relevance
“…Female sex was found to be independently associated with increased HF risk after MI in some studies, but not in others. 18,19,[21][22][23] In the studies that reported higher risk associated with female sex, the excess HF risk ranged from 15% to 34%. 6,20,24 Several reasons may explain higher HF risk in women.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Female sex was found to be independently associated with increased HF risk after MI in some studies, but not in others. 18,19,[21][22][23] In the studies that reported higher risk associated with female sex, the excess HF risk ranged from 15% to 34%. 6,20,24 Several reasons may explain higher HF risk in women.…”
Section: Gendermentioning
confidence: 99%
“…62 Several studies have shown the association of troponin or CK-MB level with MACE, including HF. 19,63,64 Yet the association of peak troponin or CK-MB with HF has not been seen in all investigations. 65,66…”
Section: Biochemical Markers Biomarkers Of Infarct Sizementioning
confidence: 99%
“…Left ventricular systolic dysfunction (LVSD) and heart failure are frequently observed after ST-segment elevation myocardial infarction (STEMI) (1)(2)(3) and patients with left anterior descending artery as the culprit vessel face even higher risks (4). Thus, it's important to optimize risk stratification after STEMI and find out novel treatment targets for preventing heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…The development of heart failure after acute coronary syndromes (ACS) is the most common complication associated with a high mortality rate 1,2. Circulating levels of C-reactive protein (CRP) have been shown to be linked to poor prognosis in patients with atherothrombotic problems, heart failure, arrhythmias, and myocarditis.3 Fourteen predictors of heart failure were studied by Ho et al4,5 Important predictors identified were older age, diabetes mellitus, valvular disease, hypertension, higher heart rate, left ventricular hypertrophy, left bundle branch block, cardiovascular disease, body mass index, smoking, gender, and dyslipidemia 4,5.…”
Section: Introductionmentioning
confidence: 99%